CROWD POLICING GUNA MENCEGAH KONFLIK TAWURAN DALAM RANGKA MEMELIHARA KAMTIBMAS YANG KONDUSIF - Dewantoro, Didi (Jurnal Ilmu Kepolisian, 2023)
Kamtibmas according to Article 1 of Law Number 2 of 2002 concerning Polri is "Dynamic condition of society, one of prerequisites for implementation of national development process in order to achieve national goals which are characterized by ensuring security, order and upholding of law so that it is achieved and maintained peace which contains ability to foster and develop potential and strength of society to prevent and overcome all forms of law violations and other forms that disturb society". In Tegal Police jurisdiction, threat of disruption to public security and order that occurs frequently and continues repeatedly, causing casualties is brawls between students. For this reason, Tegal Police need to maintain conducive security and social order by preventing brawls between students by implementing crowd policing.